2017
DOI: 10.1039/c7bm00790f
|View full text |Cite
|
Sign up to set email alerts
|

Applications of particulate oxygen-generating substances (POGS) in the bioartificial pancreas

Abstract: Type-1 Diabetes (T1D) is a devastating autoimmune disorder which results in the destruction of beta cells within the pancreas. A promising treatment strategy for T1D is the replacement of the lost beta cell mass through implantation of immune-isolated microencapsulated islets referred to as the bioartificial pancreas. The goal of this approach is to restore blood glucose regulation and prevent the long-term comorbidities of T1D without the need for immunosuppressants. A major requirement in the quest to achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 46 publications
2
45
0
Order By: Relevance
“…In keeping with the literature describing the impact of ischemia or hypoxia on human pancreatic islets (Brandhorst et al, 2016;Cantley et al, 2012;Giuliani et al, 2005;Hals, Rokstad, Strand, Oberholzer & Grill, 2013;Lai et al, 2009;Moritz et al, 2002), our results suggest that the innovative oxygen supply strategy developed in the present study may also meet the challenges of hypoxia during allotransplantation of macroencapsulated human pancreatic islets. material only in situations where hypoxia is a concern was also proposed by McQuilling, Sittadjody, Pendergraft, Farney, and Opara (2017). Similarly, in our study, the benefit of silicone-CaO 2 in preventing hypoxia-induced islet damage was observed, whereas its addition in normoxic conditions may decrease ATP content and glucose-dependent insulin secretion, and seemed to increase islet oxidative stress, as shown by increased HO-1 mRNA expression.…”
Section: Proinflammatory and Proangiogenic State Of Encapsulated Issupporting
confidence: 84%
See 4 more Smart Citations
“…In keeping with the literature describing the impact of ischemia or hypoxia on human pancreatic islets (Brandhorst et al, 2016;Cantley et al, 2012;Giuliani et al, 2005;Hals, Rokstad, Strand, Oberholzer & Grill, 2013;Lai et al, 2009;Moritz et al, 2002), our results suggest that the innovative oxygen supply strategy developed in the present study may also meet the challenges of hypoxia during allotransplantation of macroencapsulated human pancreatic islets. material only in situations where hypoxia is a concern was also proposed by McQuilling, Sittadjody, Pendergraft, Farney, and Opara (2017). Similarly, in our study, the benefit of silicone-CaO 2 in preventing hypoxia-induced islet damage was observed, whereas its addition in normoxic conditions may decrease ATP content and glucose-dependent insulin secretion, and seemed to increase islet oxidative stress, as shown by increased HO-1 mRNA expression.…”
Section: Proinflammatory and Proangiogenic State Of Encapsulated Issupporting
confidence: 84%
“…Pedraza et al () highlighted that the effect of the PDMS‐CaO 2 disk on the murine MIN6 cell line was only effective when O 2 concentration was limiting (high cell concentration and/or low O 2 tension), whereas a deleterious effect occurred in case of local excess in O 2 . The importance to use this O 2‐ generating material only in situations where hypoxia is a concern was also proposed by McQuilling, Sittadjody, Pendergraft, Farney, and Opara (). Similarly, in our study, the benefit of silicone‐CaO 2 in preventing hypoxia‐induced islet damage was observed, whereas its addition in normoxic conditions may decrease ATP content and glucose‐dependent insulin secretion, and seemed to increase islet oxidative stress, as shown by increased HO‐1 mRNA expression.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations